UPAYA MENINGKATKAN SOFT SKILL MAHASISWA MELALUI PEMBELAJARAN BERBASIS PROJECT DALAM MATA KULIAH BUSINESS PRACTICE - murtianingsih, murtianingsih (Jurnal Ilmiah Bisnis dan Ekonomi Asia, 2018)
The School of Economics of Asia is one of the universities that runs the education system. In the implementation of education system in STIE ASIA Malang using competency-based curriculum. Changes in global conditions with competition, job requirements and strategic change. STIE ASIA as one of the universities in Indonesia where the results of a review of the curriculum offered to be able to compete with the strength of the work force of the ASEAN Economic Community (MEA) that has been implemented since January 1, 2016. With the orientation on the needs and relevance of the user then applied courses that are part of the local-based curriculum project "Business Practices". Project-based learning enables students to learn which is a process whereby participants or students are self-clearing information through direct contact with others, working with groups, learning to be leaders, running a profit-oriented business, producing results in simple financial statements. Business Patterns, 2) Personal Selling, 3) Digital Marketing, 4) Business Functions. Meanwhile, soft skill as dependent variable is measured from communication ability, cooperation, confidence, and ability to be a leader.